D-Mannose Inhibits Adipogenic Differentiation of Adipose Tissue-Derived Stem Cells via the miR669b/MAPK Pathway. (10th December 2020) - Liu, Yitong; Guo, Lijia; Hu, Lei; Xie, Chen; Fu, Jingfei; Jiang, Yiyang; Han, Nannan; Jia, Lu; Liu, Yi
Abstract : The adipogenic differentiation of adipose tissue-derived stem cells (ADSCs) plays an important role in the process of obesity and host metabolism. D-Mannose shows a potential regulating function for fat tissue expansion and glucose metabolism. To explore the mechanisms through which D-mannose affects the adipogenic differentiation of adipose-derived stem cells in vitro, we cultured the ADSCs with adipogenic medium inducement containing D-mannose or glucose as the control. The adipogenic differentiation specific markers Pparg and Fabp4 were determined by real-time PCR. The Oil Red O staining was applied to measure the lipid accumulation. To further explore the mechanisms, microarray analysis was performed to detect the differences between glucose-treated ADSCs (G-ADSCs) and D-mannose-treated ADSCs (M-ADSCs) in the gene expression level. The microarray data were further analyzed by a Venn diagram and Gene Set Enrichment Analysis (GSEA). MicroRNA inhibitor transfection was used to confirm the role of key microRNA. Results . D-Mannose intervention significantly inhibited the adipogenic differentiation of ADSCs, compared with the glucose intervention. Microarray showed that D-mannose increased the expression of miR669b, which was an inhibitor of adipogenesis. In addition, GSEA and western blot suggested that D-mannose suppressed the adipogenic differentiation via inhibiting the MAPK pathway and further inhibited the expression of proteins related to glucose metabolism and tumorigenesis. Conclusion . D-Mannose inhibits adipogenic differentiation of ADSCs via the miR669b/MAPK signaling pathway and may be further involved in the regulation of glucose metabolism and the inhibition of tumorigenesis.